Targeted Variant Assessments of Human Endogenous Retroviral Regions in Whole Genome Sequencing Data Reveal Retroviral Variants Associated with Papillary Thyroid Cancer - Erik Stricker; Erin C. Peckham-Gregory; Stephen Y. Lai; Vlad C. Sandulache; Michael E. Scheurer (Microorganisms)
Papillary thyroid cancer (PTC) is one of the fastest-growing cancers worldwide, lacking established causal factors or validated early diagnostics. Human endogenous retroviruses (HERVs), comprising 8% of human genomes, have potential as PTC biomarkers due to their comparably high baseline expression in healthy thyroid tissues, indicating homeostatic roles. However, HERV regions are often overlooked in genome-wide association studies because of their highly repetitive nature, low sequence coverage, and decreased sequencing quality. Using targeted whole-genome sequence analysis in conjunction with high sequencing depth to overcome methodological limitations, we identified associations of specific HERV variants with PTC. Analyzing WGS data from 138 patients with PTC generated through The Cancer Genome Atlas project and 2015 control samples from the 1000 Genomes Project, we examined the mutational variation in HERVs within a 20 kb radius of known cancer predisposition genes (CPGs) differentially expressed in PTC. We discovered 15 common and 13 rare germline HERV variants near or within 20 CPGs that distinguish patients with PTC from healthy controls. We identified intragenic–intronic HERV variants within RYR2, LRP1B, FN1, MET, TCRVB, UNC5D, TRPM3, CNTN5, CD70, RYR1, RUNX1, CRLF2, and PCDH1X, and three variants downstream of SERPINA1 and RUNX1T1. Sanger sequencing analyses of 20 thyroid and 5 non-thyroid cancer cell lines confirmed associations with PTC, particularly for MSTA HERV-L variant rs200077102 within the FN1 gene and HERV-L MLT1A LTR variant rs78588384 within the CNTN5 gene. Variant rs78588384, in particular, was shown in our analyses to be located within a POL2 binding site regulating an alternative transcript of CNTN5. In addition, we identified 16 variants that modified the poly(A) region in Alu elements, potentially altering the potential to retrotranspose. In conclusion, this study serves as a proof-of-concept for targeted variant analysis of HERV regions and establishes a basis for further exploration of HERVs in thyroid cancer development.